2021
DOI: 10.1111/josh.13003
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perceptions of and Responses to School‐Based Body Mass Index Screening Programs—A Systematic Review

Abstract: BACKGROUND Evidence for the effectiveness of state‐mandated body mass index (BMI) screening programs in the United States has been inconclusive, and potential unintended consequences of the programs have been debated. The present review aims to understand parents' perceptions of and responses to school‐based BMI screening, and to highlight racial/ethnic differences. METHODS We systematically identified studies published January 2003‐May 2019 examining parent and/or youth perceptions of and/or responses to US s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
(185 reference statements)
0
7
1
Order By: Relevance
“…Conversely, parents were concerned about potential negative impacts, including decreased self-esteem and increased weight-related teasing (Moyers et al, 2005). Tatum et al (2021) reported that while parents largely found obesity prevention programs helpful, they were concerned about stigma, lack of privacy, and unhealthy behaviors and attitudes resulting from school-based screening. The Commission on Ending Childhood Obesity (WHO, 2016) emphasized the critical role of parents and caregivers in encouraging children to engage in healthy behaviors; thus, it is necessary to continue to educate parents to expand the role of parents in preventing childhood obesity and educate the nurses on the best way to engage with the parents to enlist their participation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, parents were concerned about potential negative impacts, including decreased self-esteem and increased weight-related teasing (Moyers et al, 2005). Tatum et al (2021) reported that while parents largely found obesity prevention programs helpful, they were concerned about stigma, lack of privacy, and unhealthy behaviors and attitudes resulting from school-based screening. The Commission on Ending Childhood Obesity (WHO, 2016) emphasized the critical role of parents and caregivers in encouraging children to engage in healthy behaviors; thus, it is necessary to continue to educate parents to expand the role of parents in preventing childhood obesity and educate the nurses on the best way to engage with the parents to enlist their participation.…”
Section: Discussionmentioning
confidence: 99%
“…Advocacy from policymakers against such weight surveillance campaigns is critical to avoid sending messages to youth that reinforce beliefs about the social (un)acceptability of high weight and exacerbate internalized weight stigma (Pearl, 2018). Indeed, findings from a recent systematic review highlighted weight stigma as a common concern of parents related to BMI reporting (Tatum et al, 2021), and few educators support in-school weight assessments or reporting students' weight status to their families (Puhl, Neumark-Sztainer, et al, 2016).…”
Section: Advocate For the Adoption Of School Wellness Programs That E...mentioning
confidence: 99%
“…Some parents and guardians in the US have reported favorable perceptions of BMI measures, school screening programs, and BMI report cards 32 . However, parents in the US have also expressed concerns about the maintenance of privacy and respect during measurement, the risk of weight stigma and unhealthy behaviors and attitudes, as well as the communication of BMI results in a non‐stigmatizing manner 35,38 . Along similar lines, Australian parents did not view schools as a setting where AM should take place because of concerns about bullying and its effects on self‐esteem, 39 and evidence suggests that these concerns are not unfounded 23,40 …”
Section: Introductionmentioning
confidence: 99%
“…33 Beyond the risks of measurement, measurement itself does not mean that a child's health status has been accurately described or that health promotion efforts will be realized. Information provided to parents is not always useful, interpretable, or actionable, 34 and neither parental follow-up with health care providers 35 nor improvements to the child's health are common. 36,37 Some parents and guardians in the US have reported favorable perceptions of BMI measures, school screening programs, and BMI report cards.…”
mentioning
confidence: 99%
See 1 more Smart Citation